Peran Undang-Undang Perlindungan Konsumen Terhadap Jasa Kurir dalam Hal Pengantaran Barang yang Cacat (Legislatif, 2026)
AbstractThe Role of Consumer Protection Law in Courier Services for the Delivery of Defective Goods. This study examines the role of consumer protection law in relation to courier services involved in the delivery of defective goods. It employs a normative juridical approach, relying on legal norms as stipulated in statutory regulations, with a primary focus on the legislative framework. The findings indicate that legal protection for couriers is not regulated within a single, specific statute, but is instead dispersed across several legal instruments, including the Indonesian Civil Code, Law Number 38 of 2009 on Postal Services, and Law Number 8 of 1999 on Consumer Protection. From a juridical perspective, couriers are positioned as third parties or authorized agents whose role is limited to delivering goods and, in certain cases, receiving payment. Consequently, they are not held responsible for defects in goods, as such liability rests with the seller as the primary business actor. Legal protection for couriers is reflected through limitations on their responsibilities and the allocation of liability to the appropriate parties. Compensation for defective goods generally falls under the responsibility of the seller and may take the form of refunds, product replacements, or other forms of compensation in accordance with applicable laws and mutual agreement. However, in practice, discrepancies persist, as couriers are often the parties who face complaints from consumers.
Keywords: Courier Services; Delivery of Defective Goods; The Role of Consumer Protection Law